HIV-1 Nef mobilizes lipid rafts in macrophages through a pathway that competes with ABCA1-dependent cholesterol efflux - Cui, Huanhuan L. (The American Society for Biochemistry and Molecular Biology, 2012)
HIV infection, through the actions of viral accessory protein Nef, impairs activity of cholesterol transporter ABCA1, inhibiting cholesterol efflux from macrophages and elevating the risk of atherosclerosis. Nef also induces lipid raft formation. In this study, we demonstrate that these activities are tightly linked and affect macrophage function and HIV replication. Nef stimulated lipid raft formation in macrophage cell line RAW 264.7, and lipid rafts were also mobilized in HIV-1-infected human monocyte-derived macrophages. Nef-mediated transfer of cholesterol to lipid rafts competed with the ABCA1-dependent pathway of cholesterol efflux, and pharmacological inhibition of ABCA1 functionality or suppression of ABCA1 expression by RNAi increased Nef-dependent delivery of cholesterol to lipid rafts. Nef reduced cell-surface accessibility of ABCA1 and induced ABCA1 catabolism via the lysosomal pathway. Despite increasing the abundance of lipid rafts, expression of Nef impaired phagocytic functions of macrophages. The infectivity of the virus produced in natural target cells of HIV-1 negatively correlated with the level of ABCA1. These findings demonstrate that Nef-dependent inhibition of ABCA1 is an essential component of the viral replication strategy and underscore the role of ABCA1 as an innate anti-HIV factor.